Demonetization: Impact on the Economy: Analyzing the impact of demonetization on the Indian economy and policy implications (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India has amongst the highest level of currencies in circulation at 12.1% of GDP. Cash on hand is an estimated at around 3.2% of household assets, higher than investment in equities, or roughly around $ 220 billion. Of this cash, 86% is in the form of Rs 500 and Rs 1,000 notes or roughly Rs 14 lakh crore ($190 billion).The argument posited in favor of demonetization is that the cash that would be extinguished would have impact on black money, fake Currency, corruption and India’s transitions towards cashless economy. While the facts arenot available to anybody, it would be foolhardy to argue that this is the only possibility. therefore evaluate the demonetizing we will discuss 3w’s.what, why, way forward. This paper elucidates that demonetization is planned script under the process of PMJDY and IDS(income disclosure system)